γ-Oryzanols of North American Wild Rice (Zizania palustris) - Aladedunye, Felix (Springer Berlin Heidelberg, 2013)
γ-Oryzanol, a natural mixture of ferulic acid esters of triterpene alcohols and sterols, are an important bioactive components present in rice bran oil. In light of the recent increase in the popularity of wild rice among consumers, and the possibility of a direct relationship between γ-oryzanol composition and its bioactivity, the oryzanol profile of major wild rice (Zizania palustris) grown in North America was studied and compared to regular brown rice (Oryza sativa L.). A total of twenty-three γ-oryzanol components were separated, identified and quantified by HPLC coupled to an Orbitrap MS. The distribution of individual γ-oryzanols was similar for all the wild rice but significantly different from those of the regular brown rice. Unlike in the regular brown rice, a significant amount of steryl caffeate and cinnamate were found in the wild rice samples. Generally, the amounts of γ-oryzanol in the wild rice were higher compared to the regular brown rice, 1,352 vs. 688 μg/g. The results from this study showed that wild rice had a more diverse γ-oryzanol composition and the higher amounts compared to the regular brown rice.